تأثير استخدام بعض النباتات الطبية وزيوتها كإضافات علفية إلى علائق الفروج على المؤشرات الصحية والإنتاجية - دلا, توفيق; شيبون, أحمد (Latakia University Journal -Biological Sciences Series, 2014)
استخدمت المضادات الحيوية لعقود في تغذية الدواجن للحد من الإصابات المرضية وتحسين أدائها الإنتاجي، ولكن تخوف المستهلك من ظهور سلالات بكتيرية مقاومة للمضادات الحيوية وتراكم بقايا هذه المضادات في المنتجات الحيوانية دفع المنظمات الغذائية لحظر استخدامها في الخلطات العلفية للفروج كمحفزات للنمو والاتجاه نحو الإضافات العلفية التجارية من منشأ نباتي ومنها النباتات الطبية وزيوتها العطرية ، حيث تمتلك الأخيرة خصائص المضاد المكروبي نظراً لاحتوائها على العديد من المركبات الفعالة مثل الثيمول والإيغونول حيث تستطيع هذه المركبات إختراق غشاء الخلية البكتيرية والتفاعل مع محتوياتها وتخريبها ، وقد وجد أن البكتيريا السالبة غرام كانت أكثر مقاومة مقارنة مع البكتيريا موجبة غرام، وتأثير مضاد للأكسدة لاحتوائها على العديد من المركبات الفعالة مثل الكارفاكرول والتوكوفيرول. حيث وجد أنها تقلل من أكسدة الدهن في الخلطة العلفية وأكسدة الأحماض الدهنية غير المشبعة في اللحم. علاوةً على ذلك فهي تحفز عملية الهضم و إنتاج الأنزيمات الهاضمة لاحتوائها على العديد من المركبات الفعالة مثل الاينوثول والايكونول. مما سبق نجد أن للنباتات الطبية وزيوتها العطرية تأثير إيجابي على الأداء الإنتاجي للفروج فقد وجد أن إضافة العديد منها للخلطة العلفية للفروج قد حسن الوزن النهائي للفروج ومعدل الزيادة الوزنية اليومية ومعامل التحويل العلفي . Antimicrobial compounds have been used for decades in poultry diets to increase performance and decrease morbidity particularly in broiler chickens. However, consumer pressure related to the potential development of antibiotic-resistant bacteria has resulted in the development of non-antibiotic feed additives that may also improve broiler erformance. In recent years, aromatic plants and their extracts have received attention as growth and health promoters. Such products have several advantages over commonly used commercial antibiotics since they are residue free and they are also, generally recognized as safe and commonly used items in the food industry. The antimicrobial properties of medical plants and their extracts have been widely reported because they consist of many active ompounds such as carvacrol, eugenol,which partition lipids in the bacterial cell wall and mitochondria, disturbing the structures and rendering them more permeable. Generally,medical plants are slightly more active against Gram-positive than Gram-negative bacteria. Medical plants are well known for their antioxidant activity and show a considerable effect on increasing the antioxidant capacity of chicken meat because they consist of many of active compounds such as tocopherol, carvacrol. Spices or their active principles have been reported to stimulate digestive secretions such as lipase, amylase and proteases.because they consist of many active compounds such as anothol, eugenol. Variable effects of medical plants and their extracts on the productive performance of broiler have been reported. The majority of experimental results indicate improved body weight gain or final body weight and feed conversion ratio.